Pengaruh Amaliah Zikir Terhadap Tingkat Ketenangan Hati Jamaah Ibu-Ibu Pengajian - Zuhrotul Baqiah; Muhtar Gojali; Naan Naan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
Increasing and decreasing the calmness of the heart greatly influences the behavior in living everyday life, both in worldly and ukhrawi's affairs. Peace of mind; one of them obtained by way of dzikir, remembering Allah SWT. Referring to the science of Sufism, dzikir can be interpreted as an activity by doing or reading a holy reading that causes someone to remember God with all his greatness. Likewise, any work that gives rise to remembering Allah is also called dzikir.This study aims to determine how much influence the remembrance of the level of peace of mind of the worshipers of woman dzikir at Al-Barokah Mosque in Bandung.The type or research method used is quantitative, where researchers analyze research data using statistical calculations. The techniques used in data collection are: 1) Observation, namely direct observation of the research object, 2) Questionnaire (Questionnaire), namely by distributing a set of statements or questions to respondents then processing data collected using IBM SPSS 23, 3) Documentation, which is to obtain additionalBased on the data obtained in the field and after the data analysis, the results obtained that the value of the correlation or relationship (R) of 0.346 and R Square of 0.120 means 12%. This value implies that there is a small or not tight correlation between dzikir and peace of mind, amounting to 0.346. And the influence of dzikir with peace of mind is classified as low at 12% while 88% the level of Peace of Heart is influenced by other variables not examined.